2020
DOI: 10.1128/jcm.00702-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xpert MTB/RIF Ultra Assay for Diagnosis of Childhood Tuberculosis: a Multicenter Accuracy Study

Abstract: A multicenter study was performed to evaluate the value of testing gastric aspirate (GA) with Xpert MTB/RIF Ultra assay (Ultra) for childhood TB detection in China. Totally, 129 children with active tuberculosis (TB) and 173 children without TB were enrolled. The sensitivity of Ultra in bacteriologically confirmed TB and probable TB cases was 87.5% (42/48) and 44.4% (36/81), respectively. The specificity of Ultra was high (99.4%, 172/173). When Ultra, culture, and acid-fast bacilli outcomes were integrated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 23 publications
2
22
0
1
Order By: Relevance
“…Sensitivity estimates vary for Ultra or Xpert compared with the reference standard of culture for the different specimen types. In our previously reported studies, the sensitivity of Ultra in bacteriological confirmed TB in children was 91% using BALF and 87.5% using gastric aspirate (GA), respectively [13,22]. In the present study, the sensitivity of Ultra using sputum in bacteriological confirmed TB was 68.4%.…”
Section: Discussionsupporting
confidence: 45%
“…Sensitivity estimates vary for Ultra or Xpert compared with the reference standard of culture for the different specimen types. In our previously reported studies, the sensitivity of Ultra in bacteriological confirmed TB in children was 91% using BALF and 87.5% using gastric aspirate (GA), respectively [13,22]. In the present study, the sensitivity of Ultra using sputum in bacteriological confirmed TB was 68.4%.…”
Section: Discussionsupporting
confidence: 45%
“…Table summarizes the characteristics of the included studies. Regarding PTB, we calculated Ultra‐pooled sensitivity and specificity of all specimens (95% CI) against culture were 78% (73%–82%) and 92% (91%–94%), respectively (Figure ) 4–13 . A high heterogeneity emerged.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies compared Ultra and Xpert MTB/RIF 4–10,12 . Ultra‐pooled sensitivity (95% CI) tended toward higher values (73%, 67%–78%) compared with Xpert MTB/RIF (66%, 60%–72%), but Ultra‐pooled specificity was lower (Ultra: 95%, 94%–96% vs. Xpert MTB/RIF: 99%, 98%–99%) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A nation-wide data from Germany reported that GA samples were used among 59% of the children which were diagnosed as pulmonary TB in the notification system, and for 34.7% of the notified patients, GA was the only reported specimen [Fiebig L et al,2014]. Data from our previous study showed that GA played important role in providing faster results, allowing an early and accurate TB diagnosis in younger children with difficulty producing sputum [Sun L et al,2020].…”
Section: Introductionmentioning
confidence: 92%